2017
DOI: 10.5530/jyp.2017.9.55
|View full text |Cite
|
Sign up to set email alerts
|

Extents of Generic Prescribing in Hospitals and Community Pharmacies for Diabetic and Hypertensive Outpatients in Eastern Region of Saudi Arabia

Abstract: Objective: As population increase, Healthcare resources are stretched and the need to reduce prescription drug spending becomes obvious. The aim of this study was to evaluate the levels of generic prescribing in place of their branded counterparts among type 2 diabetic and hypertensive outpatients in Eastern region of Saudi Arabia. Method: A cross section of 13 Hospitals and 17 Community Pharmacies located in Al Ahsa, Dhahran, Khobar and Dammam (both Government and private) were visited. Out of which 58 Physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Majority Doctors and Pharmacists are convinced that the drug is branded better outcomes to patients and this attitude has the potential to make Government policy of generic drug usage ineffective. 24 So it takes regulation and legislation from the government to be able to overcome this; thus the use and availability of drugs, especially generic drugs can be increased. The WHO HAI method is effectively used to measure the availability of drugs by using the core drug and supplementary drug references by the established reference.…”
Section: Who Haimentioning
confidence: 99%
“…Majority Doctors and Pharmacists are convinced that the drug is branded better outcomes to patients and this attitude has the potential to make Government policy of generic drug usage ineffective. 24 So it takes regulation and legislation from the government to be able to overcome this; thus the use and availability of drugs, especially generic drugs can be increased. The WHO HAI method is effectively used to measure the availability of drugs by using the core drug and supplementary drug references by the established reference.…”
Section: Who Haimentioning
confidence: 99%
“…The study found that among all prescribed medications only 26.9% were generics and the rate was higher in the governmental compared to the private hospitals. 6 The study concluded that there was an underutilization of generic medications in these 2 major health conditions in Saudi Arabia, which represent an oportunity for a cost-saving initiative. 6 The quality of medications, generics in particular, is an important constraint that has to be guaranteed before encouraging the public to use generic medications more often.…”
mentioning
confidence: 98%
“…6 The study concluded that there was an underutilization of generic medications in these 2 major health conditions in Saudi Arabia, which represent an oportunity for a cost-saving initiative. 6 The quality of medications, generics in particular, is an important constraint that has to be guaranteed before encouraging the public to use generic medications more often. The Saudi Food and Drug Authority (SFDA) is working to ensure the safety and efficacy of all medications in the country.…”
mentioning
confidence: 98%
See 1 more Smart Citation